Анализ аудита в операционной системе freebsd - Мищеряков, А. Ю. (ХНУРЕ, 2019)
In this paper we consider the audit log integrity monitoring, and protection it against unauthorized access. We consider the possibilities of an attacker to modify the audit log in order to hide his presence in the system. Some solutions to this problem and the rationale for their adoption are given. The problems that may arise in connection with the implementation of the proposed solutions are considered